Pengembalian Aset Tindak Pidana Korupsi Berdasarkan United Nation Convention Against Corruption Di Kawasan ASEAN - Sylvana Agnetha Wulan Widyastuty; Rina Shahriyani Shahrullah; Elza Syarief (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
The purpose of this study is to determine a model of international cooperation so that the assets recovery cross-border resulting from corruption in ASEAN can be more effective. Therefore, the questions in this study are: (1) how is the implementation of assets recovery cross-border as a result of corruption based on UNCAC in ASEAN including the obstacles faced and the success of assets recovery cross-border? (2) What is the solution for assets recovery cross-border resulting from corruption? This study using normative legal research methods with written studies using secondary data such as laws and regulations, legal theory, legal principles and scientific works of scholars (doctrine). The results of the study (1) The implementation of assets recovery cross-border resulting from Indonesian corruption in ASEAN was only successful for the first time in 2019 with a return of SGD 200,000 by the Corruption Eradication Commission (KPK) in collaboration with the Corrupt Practices Investigation Bureau (CPIB) Singapore. Obstacles in the implementation of assets recovery cross-border resulting from corruption: a. Structured abuse of power, b. the principle of sovereignty, c. national interest of a country and d. the Treaty on Mutual Legal Assistance in Criminal Matters (MLA ASEAN) as an international agreement is not sufficiently binding (soft law) and requires further processes such as ratification and adjustment to national criminal law. (2) Even though there is a legal umbrella for eradicating corruption related to the assets recovery cross-border resulting from corruption in the form of UNCAC and MLA ASEAN, in order to maximize the implementation of assets recovery cross-border in ASEAN, a special (bilateral) implementing agreement for assets recovery cross-border is needed in order to have more binding power. The implementation agreement is not enough, then it is also necessary to adjust and align the tools of Indonesian national law related to the asset recovery cross-border from corruption and the provision of appropriate authority for law enforcement.